Influence the bonding jumpers characteristics on the microstrip coupler lange parameters - Furmanova, Nataliya (Видавництво Львівської політехніки, 2012)
In the paper effect of the bonding jumpers characteristics as the shape, diameter, material and the number of jumpers on the microstrip coupler Lange parameters was investigated.
Keywords: microstrip line; Lange coupler; ultra-high frequency; bonding jumper